Semiconductor Processing: Novel Hybrid Organic–Inorganic Spin‐on Resist for Electron‐ or Photon‐Based Nanolithography with Outstanding Resistance to Dry Etching (Adv. Mater. 43/2013). (18th November 2013) - Zanchetta, Erika; Giustina, Gioia Della; Grenci, Gianluca; Pozzato, Alessandro; Tormen, Massimo; Brusatin, Giovanna
Abstract : A new, unique spin‐on metal‐organic resist presenting a combination of worthwhile properties is described by Giovanna Brusatin and co‐workers on page 6261. The resist shows good processability, typical of polymeric resists, direct patternability with various forms of radiation, mild post‐exposure treatment requirements, positive or negative tone development, and a selectivity greater than 100:1 with respect to the underlying silicon in a fluorine‐based continuous plasma‐etching process. The use of such materials for high‐resolution deep silicon etching is time‐ and cost‐effective compared with the pattern‐transfer materials that are generally used.